Smart Security System for Health Centers - V, Gayathri; Kanna, Suprajha; A, Umamakeswari (International Journal of Engineering and Technology, 2018)
In the modern world, Radio Frequency identification system plays a major role that automatically identifies and tracks tag attached to an object. RFID technology has  been extensively used in many areas including agriculture, manufacturing, healthcare, transportation, etc. RFID  system can be used in hospitals to increase the safety of patients by providing an RFID tag to the persons who visit them including doctors, nurses, and relatives. This method can be used along with a door lock but in the case of emergency, it becomes risky. Also, the same method can be used for secured access to pharmaceutical supplies which avoid illegal access to the medicines.  Sensor network which is the core of IoT technology can be integrated with the RFID system to make it more efficient to be deployed in several application services. In this paper, a solution is proposed that can integrate the RFID system with the IoT technology by using IR sensors which help to get rid of illegal entry or access in hospitals.